Nutritional evaluation of cassava root meal fortified with roselle seed meal as a replacement for maize on growth response and blood profile of broiler chicks - Tirmidhi, A. B.; Oguntoye, M.A; Ardo, B. A.; Akintunde, A. R.; Joshua, I. M. (Nigerian Journal of Animal Science, 2023)
A major challenge diminishing the profitability and sustainability of the poultry industry is the astronomic increase in price of feed ingredient such as maize which is progressively eroding off the expected profit margin of poultry farmers. A total of two hundred and forty (240), day-old broiler chicks were used in four weeks feeding trial to investigate the effect of fermented cassava root fortified with roselle seed meal as a replacement for maize on growth performance and blood profiles of broiler chicks. Maize is the main energy source for the control diet (T1) while the other five diets (T2, T3, T4, T5 and T6 were partially replaced with varying levels of cassava root meal – roselle seed meal (CRMRSM) mixture at 10, 20, 30, 40 and 50% inclusion rates respectively. The broiler chicks were weighed and allotted to six dietary treatments of 40 birds each. The groups were replicated four times in a completely randomized design of 10 birds per replicate. Parameters measured for growth response include: Initial weight, final weight, total weight gain, daily weight gain, total feed intake, daily feed intake and feed conversion ratio. Dietary treatments evoked significant (P < 0.05) effect on final weight, total weight gain and daily weight gain. Higher statistical (P < 0.05) values of 1153.33g and 1193.33g were recorded for final weight in the birds fed 0% and 10% CRM-RSM. Birds fed diets with 20% and 30% CRM-RSM, inclusion revealed similar statistical values 1133.33g and 1116.67g for final weight. With the exemption of neutrophil, graded level of CRM-RSM showed significant (P<0.05) influence on haematological parameters determined. Values recorded for packed cell volume PCV ranged between 38.50 – 45.00% and did not follow any specific trend. In conclusion, inclusion of cassava – roselle seed mixture up to 30% replacement level for maize improved growth performance without hazardous effect on starter broiler chicks